Methods Of Teaching Computer Literacy In Primary Grades - Shunqorbek Toshmatov (Euro Asian Journal Publishing, 2025)
This article presents ideas and considerations about the methods and effectiveness of teaching children computers using modern methods today. Teaching computer literacy to children of primary school age creates a foundation for their future success
Keywords: Computer; literacy; method; modern